Inverted follicular keratosis: A rare lesion revisited - Anubhav Chauhan; Neeraj Sharma; Lalit Gupta (Wolters Kluwer Medknow Publications, 2017)
Inverted follicular keratosis is a rare lesion of the follicular infundibulum with characteristic signs and histopathological features. It may mimic malignant lesions, especially squamous cell carcinoma and hence a high degree of suspicion is warranted whenever any patient presents with such growths.